Ensuring Sharia-Based Electoral Integrity: Lessons from Brazil’s E-Voting System for Indonesia’s Digital Democracy - Nurul Khalifah; Hasanuddin Hasim; Sudirman L; Pradana, Syafa'at Anugrah; Dirga Achmad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
The use of conventional voting systems in electoral processes continues to face significant vulnerabilities, including ballot manipulation, vote tampering, and human error. As a digital alternative, electronic voting (e-voting) offers a promising solution to enhance electoral integrity, efficiency, and transparency. While Indonesia has begun experimenting with e-voting—particularly in village head elections—it has yet to scale the system to national-level elections. This study aims to analyze Indonesia's readiness to implement a national e-voting system by drawing comparative insights from Brazil, a country that has successfully adopted e-voting in its federal elections. Using a normative legal approach and library-based research, the study evaluates the infrastructural, legal, and technological challenges facing Indonesia’s electoral modernization. The findings indicate that a major barrier to nationwide implementation lies in the technological dependency on devices such as laptops and touchscreen computers, which require stable electricity—an issue in Indonesia’s underdeveloped and remote regions. The study highlights the need for infrastructural equity and policy reform to support digital electoral governance. Theoretically, this research contributes to global debates on digital democracy, offering lessons on how socio-technical readiness shapes the adoption of e-voting in emerging democracies